2017
DOI: 10.18869/nrip.irj.15.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Time Use of Mothers of Children With an Autism Spectrum Disorder: A Comparative Study

Abstract: Objectives: Studies around the world have shown that having a child with disability impacts a mother's time use. The purpose of this study was to compare the time use of mothers of children with Autism Spectrum Disorder (ASD) with mothers of typically developing children.Methods: Eighty-four Iranian mothers (42 with ASD children and 42 with typically developing children) completed the Mothers' Time Use Questionnaire (MTUQ). Results:Mothers of ASD children spent more time doing childcare activities (P<0.001), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(51 reference statements)
2
9
0
2
Order By: Relevance
“…Personal care activities are the main self-care tasks that people usually do daily and include eating, sleeping, bathing, toileting, dressing, hygiene and mobility, and can be a challenge to children with ASD [22,23]. Our results are consistent with previous studies [7,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…Personal care activities are the main self-care tasks that people usually do daily and include eating, sleeping, bathing, toileting, dressing, hygiene and mobility, and can be a challenge to children with ASD [22,23]. Our results are consistent with previous studies [7,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…These data highlighted an imbalance in time spent on performing activities in the mothers of children with ID. Furthermore, the mothers of children with ID spent more time on childcare; these results are consistent with those of other relevant investigations [17,22,23].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the present study results revealed that the mean score of time management quality after training was higher in the intervention group, compared to the scores reported by Ahmadi Kahjough [18]; this finding may be attributed to the educational intervention used in the present study. Training improved the quality of time management in the intervention group by providing a set of skills for better control and use of time (time management) [20,22,24].…”
Section: Discussionmentioning
confidence: 99%
“…According to Silva et al (2020), these mothers felt alone in caring for their children, with difficulties in carrying out leisure activities, which led to a low quality of life. Behnia et al (2017) observed an occupational imbalance in mothers of children with ASD due to the little time spent performing occupations that are meaningful to them, such as leisure and self-care. Sen & Yurtsever (2007) found that mothers of children with ASD have their social lives altered due to caring for their children, often not managing to have time reserved for socializing with other family members.…”
Section: Discussionmentioning
confidence: 99%